ESTIMASI HARGA KONSERVASI KARBON PADA KEGIATAN A/R CDM DI HUTAN LINDUNG SEKAROH, LOMBOK TIMUR - Ridwan Fauzi; Chairil Anwar Siregar (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
Currently, incentive payment of carbon mechanism has not yet provided significant economic benefit for community who live in the surrounding forest area as the carbon price is relatively low. Consequently, potential carbon owners are likely to invest conserved carbon biomass into other products that give more profitable economic value. This paper discusses the estimation of feasible carbon selling price of Sekaroh Protection Forest based on analysis of the forest economic value approach. This study was conducted using descriptive quantitative method based on primary data sources of the Afforestation/Reforestation (A/R) Clean Development Mechanism (CDM) implementation in 2010–2013 at Sekaroh. Research results showed that based on the calculation of annual economic value (AEV), the economic value is estimated about Rp73,394,816.00 per hectare per year at the interest rate of 5.75%. Hence, a reasonable carbon price based on the economic value is US23 per ton carbon. This estimated value is significantly greater than the current prevailing carbon price that is US4.6–10 per ton carbon. Higher reasonable carbon price will attract community around the forest to keep their biomass carbon stocks in the forest, so that future business of carbon trade mechanism can be more interesting and runs better.